Here is a proof why 1 is equal to 2:
x = y
x * x = y * x
x^2 - y^2 = xy - y^2
(x+y)(x-y) = x-y(y)
x+y = y
y + y = y (remember, x = y)
y = 1; means 2 = 1
Is this right or wrong? If wrong, what step is wrong? For example, if you thought multiplying by x in the beginning was wrong, your answer would be 2.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
by this proof, on step 5, we are dividing by 0, which doesn't work. That means step 5 is wrong